Nutritional and Antinutritional Properties of Novel Milk Beverages Produced from African Breadfruit, Tigernut, Coconut and Date Fruit - O, Ogbuele Chinedu; U, Nwabueze Titus; U, Enyi Chukwunwike; Chinasa, Okorie; N, Emecheta Wisdom; C, Iwuamadi Adaobi (Journal of Food Technology Research, 2022)
Nutritional and antinutritional properties of novel milk beverages produced from African breadfruit, tigernut, coconut and date fruit were studied in this research. The plant milk beverages were formulated from these plants and compared with the quality characteristics of conventional plant milk beverage “Vita milk” which served as the control sample. Mineral and phytochemical properties were determined for the raw plant samples and beverage products. The mineral composition analysis showed that the values for the contents of calcium, magnesium, sodium, and iron (8.25, 1.42, 9.50 and 0.33) percent from the control sample were higher than the average values recorded for the same mineral content from the formulated beverage samples (3.70, 0.63, 4.94 and 0.06)percent, while the average values for the contents of potassium and phosphorous (2.72 and 5.77) from the formulated beverage samples were higher than the values from the control sample (0.33 and 0.46)percent. Out of ten phytochemicals screened in the beverage samples viz; flavonoids, alkaloids, saponins, tannins, phenols, oxalate, glycosides, carotenoids, terpenoids and steroids, seven were present in the formulated beverage samples (flavonoids, alkaloids, saponins, tannins, phenols, oxalate and glycosides), while four were present in the control sample (flavonoids, alkaloids, saponins and tannins). The study revealed that plant milk formulated from breadfruit milk, tiger nut milk, coconut milk and date fruit juice gave products that are comparable to the conventional soy bean based vita milk in terms of their nutritional composition.